OBTAINING BIODEGRADABILITY FILM OF CASHEW (ANACARDIUM OCCIDENTALE) RESIDUE FROM THE CARIRI REGION FOR FOOD - Alves Palmeira, Isis; Ferreira Rodrigues, Raimundo Ruan; Duarte da Silva, Carmen Luce; Rodrigues Machado, Adriana; Navarrete Toledo, Antônio Matias; Rodrigues Machado, Maria Inês (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2024)
Brazil is one of the leading food producers, but it still faces the reality of food waste. The use of fruit residues in the production of new products is a clean and sustainable technological alternative. The objective of this work was to characterize biodegradable films produced from natural raw materials and dehydrated organic cashew residues, in terms of thickness, weight, density, permeability, solubility, transparency, and moisture. The results obtained in the analyses were: Thickness: 0.046 cm; Weight: 0.039 g/cm²; Density: 0.85 g/cm³, Permeability: 372.4 g/(dia.cm²), Solubility: 29.33%, Transparency, measured in Transmittance 0.48 nm and Humidity: 9%. From the data obtained, we can infer that the films produced are of low thickness and weight which allows its high flexibility, ideal for food coating, the density found is lower than the density of water, which is an important parameter for its biodegradation, the permeability found was also low. Being an important characteristic because it is the one that allows the interaction with the external environment when the product is stored and, thus, configures the protection to the product, the solubility analysis revealed a low value similar to those found in the literature, which is ideal for the packaging of food products rich in water activity, Thus, a film with low humidity provides even more preservation to food. The films obtained presented favorable characteristics for food preservation.